A Cross-Sectional Examination on the Interplay of Filipino American Demographic Characteristics upon their Self-Reported Experiences of Colonial Mentality and Depression - Sharpe, Rhiana; Goswell, Katanya Good; McIntyre, Kristol; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2025)
This study’s primary purpose was to conduct a cross-sectional examination of the interplay among various Filipino American demographic characteristics (ex., gender identity, education level, and cultural generation identity) upon their experiences of colonial mentality and depression. An online survey was distributed through social media (Reddit and Instagram), comprising the Colonial Mentality Scale (David & Okazaki, 2006) and the PHQ-9 (Pfizer, 1999). A total of 63 participants were used in the study. One of the key findings of the current research study is that cis male Filipino Americans reported the highest mean colonial mentality score as compared to their cis female Filipino American counterparts and their LGBTQ Filipino American counterparts. Filipino Americans who had less than a college-level education had the highest level of self-reported depression as compared to Filipino Americans who had completed a college-level education or greater. There was also an interaction effect where the 1st generation cis male Filipino Americans reported higher mean depression scores as compared to 2nd generation cis male Filipino American counterparts. In contrast, the 1st generation cis female Filipino Americans report lower mean depression scores as compared to their 2nd generation cis female Filipino American counterparts. Similarly, the 1st generation LGBTQ Filipino Americans report lower mean depression scores as compared to their 2nd generation LGBTQ Filipino American counterparts. The research findings are discussed in the context of other prior research on cultural mentality and depression among Filipino Americans, along with how this informs culturally competent mental health treatment approaches and considerations when working with the Filipino American population.